UPAYA ORANG TUA DALAM MENATA SITUASI PENDIDIKAN DIDALAM KELUARGA : Studi Tentang Nilai-Nilai yg Mendasari dan Mengarahkan Upaya Orang tua yang diserap Anak Dalam Situasi Pendidikan di Keluarga Masyarakat Banda Aceh - Kadarusmadi, - (2000)
The objective of this research is to discover, reveal, and analyze the parents* efforts in a nuclear family who live in Banda Aceh in managing educational situations in their family, i.e., the efforts to help children in choosing, understanding, and developing the fundamental values for themselves. The efforts are. realized through real actions. The parents' actions reflect the basic values that are continuously promoted in the family life, namely the situations that are shared by the children and their parents, and where communication or social interaction between them takes place. It is through this interaction that the basic values are transformed. The research is also to discover, expose, and analyze the fundamental structure which is essential to the efforts.By using phenomenology as the theory and method, the research was carried out to study three nuclear families in Banda Aceh. The three nuclear families are relatively young in age and in marriage, their children are still studying in elementary school. The economic welfare, education, and the jobs of their parents are different. From the observation, it was found that conditions in the family reflect educational backgrounds, jobs, and the past experience of the parents. However, their efforts in the family life are similar. And the condition of each family creates different nuances for the realization of efforts chosen by the parents.The efforts to integrate what they say and what they do are effective efforts to make children accustomed to doing things, such cleanliness, praying to Allah the Almighty, and fasting as practised by the parents as a model for the children in maintaining the basic values. Besides, other efforts such as asking, explaining, forbidding, suggesting, rewarding, appreciating, and tool maintaining are an integrated part of managing educational situation in the family. In practice, both father and mother are models